Assessment of Timber–Concrete Connections Made with Glued Notches: Test Set‐Up and Numerical Modeling. Issue 2 (5th April 2012) - Monteiro, S.R.S.; Dias, A.M.P.G.; Negrão, J.H.J.O.
<x xml:space="preserve">Abstract</x> The aim of this study is to analyze the mechanical behavior of timber–concrete connections established through glued notches, as well as the parameters that may affect it, specifically in the experimental shear test procedure. With these objectives in mind, a database based on a literature survey was created, identifying different shear test set‐ups. In addition, a numerical approach was also adopted, based on experimental results. A numerical finite element method model was developed in order to describe the behavior of this type of connection. To validate the model, three sets of experimental tests were used, differing according to the notch material, the concrete class and the set‐up's geometry. Using this model, parametric studies were developed to analyze the effects of the material and geometrical parameters and support conditions. The database showed that double‐shear tests were the most common experimental test set‐up. The numerical modeling allowed a good approximation to a connection's linear‐elastic behavior. Parametric studies showed that the parameter with the greatest effect on a connection's stiffness was the modulus of elasticity of timber, in contrast with the support conditions. The locations chosen to measure displacements on timber and concrete elements were also shown to affect the calculated connection stiffness.